Histological research of hepatoprotective activity of tablets Lavaflam in rats with subchronic hepatitis - M. A. Aslanian; L. A. Bobrytska; N. L. Bereznyakova; O. S. Shpychak; V. I. Hrytsenko; T. A. Germanyuk; T. I. Ivko (Zaporožskij Medicinskij Žurnal)
Hepatobiliary system diseases are medical and social problem at the present time. Important issue is the development of a new complex of herbal medicine and its pharmacoeconomic study.